Hyperprolactinemia in women: diagnostic approach - Glezer, Andrea; Garmes, Heraldo Mendes; Kasuki, Leandro; Martins, Manoel; Elias, Paula Condé Lamparelli; Nogueira, Vania dos Santos Nunes [UNESP]; de Sá Rosa-E-Silva, Ana Carolina Japur; Maciel, Gustavo Arantes Rosa; Benetti-Pinto, Cristina Laguna; Nácul, Andrea Prestes (Federação das Associações de Ginecologia e Obstetrícia, 2024)
The National Specialized Commission on Endocrine Gynecology of the Brazilian Federation of Gynecology and Obstetrics Associations (FEBRASGO) and the Department of Neuroendocrinology of the Brazilian Society of Endocrinology and Metabolism (SBEM) endorse this document. Content production is based on scientific evidence on the proposed theme and the results presented contribute to clinical practice.